Creating a Formula for Success Why English Language Learner Students Are Dropping out of School, and How To Increase Graduation Rates. - Advocates for Children of New York, Inc., Long Island City.; Advocates for Children of New York, Inc., Long Island City. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2002)
This report reviews statistical data collected by the New York City (NYC) Board of Education (BOE) and New York State Education Department documenting the rise in school dropout rates among English Language Learners (ELLs) and their unacceptable educational outcomes, incorporating students' comments gathered during focus groups held with NYC high school ELLs in 2001. The report documents the failure of the State Education Department and NYC BOE to provide adequate support and educational intervention services in accordance with established laws and policies to ensure school success for ELLs. Factors associated with increased academic risk for ELLs included failure of schools to provide additional required English classes or have trained, certified ESL and bilingual teachers; lack of ESL curricula tied to new standards; lack of extended day, weekend, and year-round programs for late arriving ELLs and other at-risk ELLs; very high levels of dropouts in certain high schools; poor preparation for high school by many middle schools; and one-size-fits-all graduation standards. Students were often encouraged by school staff to pursue GEDs instead of regular high school diplomas. Key recommendations to improve the education of ELLs, increase graduation rates, and lower dropout rates include increasing school accountability for ensuring that schools succeed and improving ESL instruction. (Contains 58 references and 7 tables.) (SM)
Availability: Advocates for Children of New York, Inc., 151 West 30th Street, 5th Floor, New York, NY 10001. Web site: http://www.advocatesforchildren.org.
Sponsoring Agency: Robert Sterling Clark Foundation, Inc., New York, NY.
ERIC Note: Also prepared by The New York Immigration Coalition.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Academic Standards; Bilingual Students; Dropout Rate; Dropouts; Educational Quality; English (Second Language); Equal Education; High Risk Students; High Schools; Immigrants; Language Minorities; Low Achievement; New York City Board of Education; Student Support Services; Reports, Research